2021
DOI: 10.3390/cancers13225690
|View full text |Cite
|
Sign up to set email alerts
|

Role and Clinical Utility of Cancer/Testis Antigens in Head and Neck Squamous Cell Carcinoma

Abstract: Cancer/testis (CT) antigens exhibit selective expression predominantly in immunoprivileged tissues in non-pathological contexts but are aberrantly expressed in diverse cancers. Due to their expression pattern, they have historically been attractive targets for immunotherapies. A growing number of studies implicate CT antigens in almost all hallmarks of cancer, suggesting that they may act as cancer drivers. CT antigens are expressed in head and neck squamous cell carcinomas. However, their role in the pathogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 191 publications
(170 reference statements)
1
4
0
Order By: Relevance
“…Although the frequency of expression of the same CTA varied in different cancer types, MAGE-A and PRAME were more commonly expressed in these three cancer types, in contrast to KK-LC-1 and NY-ESO-1, which were less frequently expressed. In addition to KK-LC-1, six other CTAs have been studied in the literature for their expression in HNSC [22]. The present study showed that KK-LC-1 was expressed at a low rate of 3% in HNSC.…”
Section: Discussionsupporting
confidence: 48%
“…Although the frequency of expression of the same CTA varied in different cancer types, MAGE-A and PRAME were more commonly expressed in these three cancer types, in contrast to KK-LC-1 and NY-ESO-1, which were less frequently expressed. In addition to KK-LC-1, six other CTAs have been studied in the literature for their expression in HNSC [22]. The present study showed that KK-LC-1 was expressed at a low rate of 3% in HNSC.…”
Section: Discussionsupporting
confidence: 48%
“…CTA genes, including MAGEs, have been recently excellently reviewed [6,7,70]. Therefore, we only briefly indicate some functions of selected CTA genes which provide key points for our further analysis of GG STRING PPI networks.…”
Section: The Mage Protein Oncogene Family Functions In Gametogenesis ...mentioning
confidence: 99%
“…It is enriched with the MAGE group and related reproduction processes. In particular, all these genes are also potential oncogenes [5][6][7]. The densely intertwined CTA-MAGE core of the network (predominantly from the long arm Xq27-28, (see details in Figure 4)) drives spermatogenesis from the proliferation of spermatogonial cells, including the FATE1 (Xq28) gene.…”
Section: String Network Analysis (Continuation) Strata 10-16mentioning
confidence: 99%
See 2 more Smart Citations